the The National School of Instructors against the culture of gender equality in SENA - Contreras Guerra, Alfa María
Based on Human Rights, the peace agreement was signed in Colombia. This article arises from this new reality, addressing the following questions: Starting from our longing for a different Colombia, can we build relationships of friendship, trust and coexistence ?; What is required to make the decision to abandon the attacks on women, who, in the midst of the war, in addition to being victims, are called to move forward with their families because their partners have been in the midst of the country's conflict? In order to answer, even partially, these questions, the text highlights some lessons learned through the work on gender equality of the National School of Instructors of SENA.